Pengaruh Kepercayaan Merek, Promosi Dankepuasan Konsumen Terhadap Keputusan Pembelian Sepeda Motor Honda (Studi Kasus Pada Mahasiswa Manajemen Universitas Islam Malang Angkatan 2018) - Muhammad Risky Syahdillah; Siti Asiyah; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to analyze, describe and determine the effect of brand trust, promotion and consumer satisfaction on purchasing decisions for Honda motorcycles, a case study on undergraduate students of Management Faculty of Economics and Business class of 2018 Islamic University of Malang. This type of research uses explanatory research using a quantitative approach and data collection techniques used in this study are questionnaire data and use statistics as an analysis technique. In this study, the sample used is 106 students who will be the object of research. In this study the number of population is not known with certainty so that in determining the number of samples using the formula from Malhotra. Where according to Asnawi and Masyhuri (2011:143) the Malhotra formula sets the number of samples or populations that are not counted at least 4 or 5 x the number of indicators used in this study. The number of variables set is 4 variables, which are 3 independent variables and 1 dependent variable. From the number of variables obtained a total of 15 indicators. Then the calculation of the number of samples required are: 15 x 5 = 75 samples. In this study using a porposive sampling technique. Where the results of this study indicate that brand trust, promotion and purchasing decisions simultaneously and significantly affect the satisfaction of purchasing decisions for Honda motorcycles, brand trust has a significant effect on purchasing decisions on Honda motorcycles, promotion has no significant effect on customer satisfaction on brand motorcycles. Honda, and consumer satisfaction has no significant effect on customer satisfaction on Honda motorcycles. Keywords: Brand Trust, Promotion And Consumer Satisfaction And Purchase Decisions